Re-branding extension for a 21st century agriculture : in a nutshell (IICA St. AugustineTT, 2009)
Synthesises the main issues to contribute to te ongoing dialogue and search for strategies to re-brand extension in the 21st century.
Keywords: AGRICULTURAL EXTENSION